An Infectious Silver Lining: Is There a Positive Relationship Between Recovering From a COVID Infection and Psychological Richness of Life? - Dahlen, Micael; Thorbjørnsen, Helge (Frontiers in Psychology, 2022)
This paper draws from the recent literature on psychological richness of life (PRL), conceptualized as a third dimension of a good life which would be particularly desirable when happiness or meaning in life cannot be satisfactory attained, to investigate whether recovering from a COVID infection could be associated with PRL. We hypothesize that people who have recovered from being infected by the virus rate their PRL higher than those who have not been intected. Two cross-sectional studies (n = 937, and n = 1,012) support the hypothesis, and also found that people who recovered from a COVID infection were less prone to want to delete the pandemic time period from their life line and reportered lower levels of death anxiety. The findings have implications for coping both on a societal and individual level, by changing perspectives and valuing the richness of positive as well as negative experiences, as well as counteracting repetitiveness and tedium and stimulating new experiences and reflection. The findings also have implications for future research on well-being, which could be informed by expanding the perspective from living well to a life well-lived, and future research on PRL and coping in terms of investigating causalities and interaction effects.